BULLYING DI LINGKUNGAN SEKOLAH: DAMPAKNYA TERHADAP KESEHATAN MENTAL DAN PRESTASI SISWA - Catur Priyanto (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Bullying in schools has become a critical issue with profound impacts on students’ psychological well-being and academic performance. This study aims to identify the forms of bullying, analyze their effects on mental health and learning outcomes, and propose preventive strategies applicable within educational settings. The research employs a literature review method by analyzing relevant sources including books, scholarly articles, and institutional reports. The findings reveal that bullying may occur in physical, verbal, social, and digital forms, all of which significantly increase the risks of depression, anxiety, low self-esteem, as well as decreased learning motivation and academic achievement. This study highlights the crucial roles of schools, parents, and communities in establishing a safe and inclusive learning environment free from violence. Recommendations emphasize the importance of implementing strict anti-bullying policies, character education, and cross-sector collaboration to promote students’ psychological well-being and academic success.